Expression Analysis of Long Non-Coding RNAs Related With FOXM1, GATA3, FOXA1 and ESR1 in Breast Tissues - Hassani, Bita; Taheri, Mohammad; Asgari, Yazdan; Zekri, Ali; Sattari, Ali; Ghafouri-Fard, Soudeh; Pouresmaeili, Farkhondeh (Frontiers in Oncology, 2021)
Breast cancer is the most common neoplasm among females. Estrogen receptor (ESR) signaling has a prominent impact in the pathogenesis of breast cancer. Among the transcription factors associated with ESR signaling, FOXM1, GATA3, FOXA1 and ESR1 has been suggested as a candidate in the pathogenesis of this neoplasm. In the current project, we have designed an in silico approach to find long non-coding RNAs (lncRNAs) that regulate these transcription factors. Our systems biology method led to the identification of APTR, AC144450.1, linc00663, ZNF337.AS1, and RAMP2.AS1 lncRNAs. Subsequently, we assessed the expression of these genes in breast cancer tissues compared with the adjacent non-cancerous tissues (ANCTs). Expression of GATA3 was significantly higher in breast cancer tissues compared with ANCTs (Ratio of mean expressions (RME)=4.99, P value=3.12E-04). Moreover, expression levels of APTR, AC144450.1, and ZNF337.AS1 were elevated in breast cancer tissues compared with control tissues (RME=2.27, P value=5.40E-03; Ratio of mean expressions=615.95, P value=7.39E-19 and RME=1.78, P value=3.40E-02, respectively). On the other hand, the expression of RAMP2.AS1 was lower in breast cancer tissues than controls (RME=0.31, P value=1.87E-03). Expression levels of FOXA1, ESR1, and FOXM1 and linc00663 were not significantly different between the two sets of samples. Expression of GATA3 was significantly associated with stage (P value=4.77E-02). Moreover, expressions of FOXA1 and RAMP2.AS1 were associated with the mitotic rate (P values=2.18E-02 and 1.77E-02, respectively). Finally, expressions of FOXM1 and ZNF337.AS1 were associated with breastfeeding duration (P values=3.88E-02 and 4.33E-02, respectively). Based on the area under receiver operating characteristics curves, AC144450.1 had the optimal diagnostic power in differentiating between cancerous and non-cancerous tissues (AUC=0.95, Sensitivity=0.90, Specificity= 0.96). The combination of expression levels of all genes slightly increased the diagnostic power (AUC=0.96). While there were several significant pairwise correlations between expression levels of genes in non-tumoral tissues, the most robust correlation was identified between linc00663 and RAMP2.AS1 (r=0.61, P value=3.08E-8). In the breast cancer tissues, the strongest correlations were reported between FOXM1/ZNF337.AS1 and FOXM1/RAMP2.AS1 pairs (r=0.51, P value=4.79E-5 and r=0.51, P value=6.39E-5, respectively). The current investigation underscores the importance of APTR, AC144450.1 and ZNF337.AS1 in the pathogenesis of breast neoplasms.